Perancangan Rumah Sakit Hewan Jakarta Pendekatan Arsitektur Hijau - Praya Darasia (TERAKOTA : Jurnal Poster Arsitektur, Interior dan Rancang Kota, 2023)
Designing the Jakarta Animal Hospital building to accommodate functions such as animal healthcare, animal care, education, and recreation. An Animal Hospital is a building or facility dedicated to caring for sick animals and nursing them back to health.Green architecture, also known globally as green architecture, is one architectural approach that focuses on environmentally friendly design. In the basic concept of designing the Jakarta Animal Hospital, the use of green architecture is emphasized, where the concept prioritizes creating a sustainable building that utilizes natural energy sources. The design of the Jakarta Animal Hospital depicts a hospital that is friendly towards humans as visitors or caretakers, animals as patients, and the environment as a supporting and integral factor in the design concept. This reflects a Hospital that provides healthcare services for animals. If the Jakarta Animal Hospital has sufficient and supportive facilities, it can contribute to the well-being of humans, animals, and the environment.